Assessment of genetically modified maize DP51291 (application GMFF‐2021‐0071) - EFSA Panel, Genetically Modified Organisms (GMO); Casacuberta, Josep; Barro, Francisco; Braeuning, Albert; Cubas, Pilar; de Maagd, Ruud; Epstein, Michelle M.; Frenzel, Thomas; Gallois, Jean‐Luc; Koning, Frits; Messéan, Antoine; Moreno, F. Javier; et al. (EFSA, 2024)
Genetically modified maize DP51291 was developed to confer control against susceptible corn rootworm pests and tolerance to glufosinate-containing herbicide; these properties were achieved by introducing the ipd072Aa, pmi and mo-pat expression cassettes. The molecular characterisation data and bioinformatic analyses do not identify issues requiring food/feed safety assessment. None of the identified differences in the agronomic/phenotypic and compositional characteristics tested between maize DP51291 and its conventional counterpart needs further assessment, except for phosphorus in forage and manganese, proline, oleic acid (C18:1) and linoleic acid (C18:2) in grain, which do not raise safety and nutritional concerns. The GMO Panel does not identify safety concerns regarding the toxicity and allergenicity of the IPD072Aa, PAT and PMI proteins as expressed in maize DP51291 and finds no evidence that the genetic modification would change the overall allergenicity of maize DP51291. In the context of this application, the consumption of food and feed from maize DP51291 does not represent a nutritional concern in humans and animals. The GMO Panel concludes that maize DP51291 is as safe as its conventional counterpart and non-GM maize varieties tested, and no post-market monitoring of food/feed is considered necessary. In the case of accidental release of viable maize DP51291 grains into the environment, this would not raise environmental safety concerns. The post-market environmental monitoring plan and reporting intervals are in line with the intended uses of maize DP51291. The GMO Panel concludes that maize DP51291 is as safe as its conventional counterpart and the tested non-GM maize varieties with respect to potential effects on human and animal health and the environment.
Keywords: DP51291; genetic engineering; GM; import and processing; IPD072Aa; maize (Zea mays); PAT; PMI